# Help me please with math

Question

Answer:

Answer:given below ↓Explanation:2)y = x - 4y = -x + 2as they are equal: -x + 2 = x - 4-x - x = -4 - 2-2x = -6x = 3y = -x + 2y = -3 + 2y = -1solutions: (3,-1)3)y = 3x + 1y = 5x - 3as y are equal: 5x - 3 = 3x + 15x - 3x = 1 + 32x = 4x = 2y = 3x + 1y = 3(2) + 1y = 6 + 1y = 7solutions: (2,7)4)2x + y = 8y = x - 7insert equation x - 7 in replace of y in equation 12x + x - 7 = 83x - 7 = 83x = 15x = 5y = x - 7y = 5 - 7y = -2solution's: (5,-2)
solved

general
10 months ago
2273